100% -CONTROL OF PRODUCTION QUALITY: ADVANTAGES AND DISADVANTAGES - E. A. Peretjagina; l. A. Feklistova (Литьë и металлургия)
The methods of statistical control by alternative and quantitative attribute are described. Analysis of level of production faultiness AQL and index of conformance Pp, PpK is carried out.